The use of portfolio as an assessment tool in the Malaysian L2 classroom - Swaran Singh, Charanjit Kaur; Abd. Samad, Arshad (Macrothink Institute, 2013)
This article focuses on the use of portfolio as an assessment tool for learning in two Malaysian secondary ESL classrooms. Participants included nine experienced lower and upper secondary school classroom ESL teachers who had utilised portfolio as an assessment tool in their classrooms. A qualitative research design was employed within the interpretive research paradigm as to provide an in-depth description of ESL teachers’ understanding of the use of portfolio as an assessment tool in the classroom. The interview data were used for triangulating data obtained from the classroom observations. Data collected through both techniques were transcribed and analyzed manually. The nine ESL teachers reported that student’s self-reflection and self-assessment helped them to improve their instruction in the classroom. Moreover, the ESL teachers found students showed progress in learning via supplementary exercises which were assessed and then graded. The teachers disclosed that the core features of a portfolio assessment include purpose, content and structure which were considered crucial to bring about effective results of student learning. The qualitative findings contribute to a better understanding of the use of portfolio as an assessment tool and have some implications for teaching and assessment.